Comprehensive Characterization of Arterial and Cardiac Function in Marfan Syndrome—Can Biomarkers Help Improve Outcome? - Weismann, Constance G.; Hlebowicz, Joanna; Åkesson, Anna; Liuba, Petru; Hanseus, Katarina (Frontiers in Physiology, 2022)
Background: Marfan Syndrome (MFS) has been associated with increased aortic stiffness and left ventricular dysfunction. The latter may be due to the underlying genotype and/or secondary to aortic stiffening (vascular-ventricular interaction). The aim of this study was to characterize arterial and cardiac function in MFS using a multimodal approach. Methods: Prospective observational study of MFS patients and healthy controls. Methods included echocardiography, ascending aortic distensibility, common carotid intima media thickness [cIMT], parameters of wave reflection, carotid-femoral pulse wave velocity [cfPWV]), reactive hyperemia index [RHI] and biomarker analysis (Olink, CVII panel) . Results: We included 20 patients with MFS and 67 controls. Ascending aortic distensibility, cIMT and RHI were decreased, while all parameters of arterial wave reflection, stiffness and BNP levels were increased in the MFS group. Both systolic and diastolic function were impaired relative to controls. Within the MFS group, no significant correlation between arterial and cardiac function was identified. However, cfPWV correlated significantly with indexed left ventricular mass and volume in MFS. Bran natriuretic peptide (BNP) was the only biomarker significantly elevated in MFS following correction for age and sex. Conclusions: MFS patients have generally increased aortic stiffness, endothelial dysfunction and BNP levels while cIMT is decreased, supporting that the mechanism of general stiffening is different from acquired vascular disease. CfPWV is associated with cardiac size, blood pressure and BNP in MFS patients. These may be early markers of disease progression that are suitable for monitoring pharmacological treatment effects in MFS patients.